Evidence for Fluid Pressurization of Fault Zones and Persistent Sensitivity to Injection Rate Beneath the Raton Basin - Mohammadreza Jamalreyhani; Ruijia Wang; Brandon Schmandt; Andres Felipe Peña Castro; Margaret Elizabeth Glasgow (Geophysical Research Letters, 2025)
Abstract Subsurface wastewater injection has increased the seismicity rate within the Raton Basin over more than two decades, with the basin‐wide injection rate peaked between 2009 and 2015. To understand the evolution of injection‐induced earthquakes, we systematically analyzed 2016–2024 broadband recordings with a machine‐learning‐based phase picker and constructed a catalog with 95,993 earthquakes (−1 ≤ ML ≤ 4.3). We then inverted for full centroid moment tensors (CMT) for 90 ML ≥ 2 events, with a special interest in constraining the non‐double‐couple components via probabilistic metrics. Both relocations and CMT solutions support basement‐rooted normal faults, including graben and half‐graben structures. Furthermore, we observe the non‐double‐couple components that imply elevated pore pressure in the fault zones. An earthquake cluster emerged in the north‐central basin in 2023, preceded by ∼1‐yr of increased injection volume from wells within 15 km. Despite a basin‐wide decrease in the injection volume, we highlight the persistence of seismicity that remains sensitive to injection rates within the Raton Basin.